Application of technology for improving community economic welfare through fish cultivation in the bioflok pool - Nurhayati; Tambunan, Manggara M; Wahyuni, Dini (Talenta Publisher, 2019)
UKM Mandiri Jaya is a community group effort that has not been economically productive, but has a strong desire to become an entrepreneur. Members of these SMEs are made up of economically weak communities. They have a very low income. Daily necessities of life are obtained through farming and catfish farming. The effort is carried out on arable land and the home page. Agricultural products are sold, but are not able to meet the increasing needs. Catfish farming is also carried out on a small scale because it is constrained by the high price of feed on the market. With the aim to develop the business of fish farming, SMEs have been given fish seeds, materials and pellet making equipment and fish feed making machines. A fish feed machine is needed so that farmers can increase their income by utilizing existing ingredients as a fish feed composition. Partners have been trained so as to be able to make their own fish feed from quality ingredients and partners have the ability to use the machines provided. Through the feed produced by the use of a given machine, the better fish growth. More fish yields resulting in an increase in income for these partners.